2020
DOI: 10.4018/ijcbpl.2020010104
|View full text |Cite
|
Sign up to set email alerts
|

Continued Usage and Dependency of Smartphones

Abstract: Smartphones have become an integral part of everyone's life. Being a powerful communication device, the number of subscribers is persistently increasing every year. Younger generation are often the early adopters of smartphones. Because of its educational and entertaining options students have adopted them easily. This study aims to identify the factors that lead to student dependency on smartphones and thus leading to continued usage. The data was collected from undergraduate students and was analysed using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Unlike educational smartphone use, distractive smartphone use was not successfully modeled by the fsQCA procedures. A recent structural equation modeling study found that Indian college students' continued intention of using smartphones was predicted by smartphone dependency, which was predicted by social influence, social needs, performance expectancy and convenience measurements (Rosaline & Pradesh, 2020). Earlier theorists have conceptualized disordered mobile phone use behaviours with a pathway model (Billieux et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike educational smartphone use, distractive smartphone use was not successfully modeled by the fsQCA procedures. A recent structural equation modeling study found that Indian college students' continued intention of using smartphones was predicted by smartphone dependency, which was predicted by social influence, social needs, performance expectancy and convenience measurements (Rosaline & Pradesh, 2020). Earlier theorists have conceptualized disordered mobile phone use behaviours with a pathway model (Billieux et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by Olufadi's recent research (Olufadi, 2015), the current study integrated theories from consumer psychology, abnormal psychology, and educational psychology and proposed a three-component framework for understanding smartphone use behaviour in learning settings. continued intention of using smartphones was predicted by smartphone dependency, which was predicted by social influence, social needs, performance expectancy and convenience measurements (Rosaline & Pradesh, 2020). Earlier theorists have conceptualized disordered mobile phone use behaviours with a pathway model (Billieux et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…eHealth is an umbrella term that refers to the use of modern information and communication technology to deliver health care [ 14 ]. A branch of eHealth showing growth in development is mobile health (mHealth) [ 15 ] as a result of the increasing use of mobile devices, partnered with improvements in technology development (eg, smartphones), with predictions that device availability will increase over the next decade [ 16 ]. According to the 2019 Ofcom report, the UK telecom sector generated £33.8 billion (US $45.03 billion), with mobile devices accounting for 51% of the total revenue.…”
Section: Introductionmentioning
confidence: 99%
“…Technology-based interventions for pain management, such as mobile health interventions, are an effective way of providing such self-management skills and education to both patients and health care providers [12,13]. This branch of health care is becoming increasingly popular due to the high availability of smartphone devices [14]. Mobile health has helped to increase the accessibility and affordability of health care for those living in rural locations or on low incomes [15].…”
Section: Introductionmentioning
confidence: 99%